Kosmos sebagai Teofani: Rekonstruksi Ruang Liturgis dalam Kosmologi St. Maximus the Confessor - Marlina Martinus; Hendi Wijaya (JOURNAL of THEOLOGICAL STUDENTS, 2026)
The cosmos as a theophany and a liturgical space is one of the central themes in the theology of St. Maximus the Confessor. Amid various modern approaches that tend to view the universe as a neutral reality detached from theological meaning, Maximus offers a cosmological vision centered on Christ as the divine Logos. This study aims to analyze St. Maximus’ understanding of the cosmos as theophany and liturgical space through the concept of Logos-logoi, the role of humanity as cosmic priests, and the ultimate purpose of creation in telos and theosis. The method employed is a literature review using a descriptive-analytical approach to various sources discussing Maximus’s cosmology. The results of the study indicate that the cosmos is not understood as a neutral or static reality, but rather as a sacred space that reveals the presence of God and moves toward union with the Logos through the Incarnation of Christ. Within this framework, all of creation participates in a cosmic liturgy that directs everything toward God. This study affirms Maximus’s cosmology presents a synthesis of creation theology, Christology, anthropology, and cosmic liturgy Christ centered theological vision.